If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4.5x + 4 = 7x + -6 Reorder the terms: 4 + 4.5x = 7x + -6 Reorder the terms: 4 + 4.5x = -6 + 7x Solving 4 + 4.5x = -6 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 4 + 4.5x + -7x = -6 + 7x + -7x Combine like terms: 4.5x + -7x = -2.5x 4 + -2.5x = -6 + 7x + -7x Combine like terms: 7x + -7x = 0 4 + -2.5x = -6 + 0 4 + -2.5x = -6 Add '-4' to each side of the equation. 4 + -4 + -2.5x = -6 + -4 Combine like terms: 4 + -4 = 0 0 + -2.5x = -6 + -4 -2.5x = -6 + -4 Combine like terms: -6 + -4 = -10 -2.5x = -10 Divide each side by '-2.5'. x = 4 Simplifying x = 4
| 3x/2-1=x/7 | | -3x-9x=-3 | | 8y=-6x+24 | | -9y+2x=11 | | T+97=513 | | y^2+1y= | | 3y^2+7y^2+2y^3= | | 7(-21)-3y=-21 | | -4b-5+2d=10 | | 21=6-x-4 | | 2.5y+0z=-2.5 | | 7(7p+1)-4p=13(3p-2) | | y=5(2x-9) | | 1/7-51/2=9/14 | | 72500+10.50x=2500 | | .25(60+16s)=0.3333333333333333(45+12s) | | a^2-15=0 | | 5y-2y+9y=-16 | | 18=5x-3x | | 7-3n=-4n+1 | | 3y^2+9y=0 | | 10-8r=-6r-6 | | 4(x+7)=-4 | | 12-5n=h+6 | | 6x+2y=19 | | 11+6k=1+4k | | 8t+3/5=9 | | y=2/3x | | 3x-11=2(y-4) | | -3z-4=2z-24 | | 3+6x=7x+6-1 | | 17=119/w |